Fungistatic effect of Gracilaria verrucosa on phospholipase enzymes and the cell surface hydrophobicity of Candida albicans - Gani, Basri A.; Andayani, Ridha; Batubara, Fitri Yunita; Ifwandi, Ifwandi; Syafriza, Dharli; Herlambang, Muhammad Mas'ud; Fathirah, Shiti Alya; Rifki, Ayudia (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Candida albicans (C. albicans) was reported as a primary cause of oral candidiasis. Phospholipase enzymes and cell surface hydrophobicity (CSH) are involved in the pathogenesis of its infection. Gracilaria verrucosa (G. verrucosa) is reported to contain flavonoids, tannins, and phenolic compounds, which can inhibit the development of C. albicans. Purpose: The study analyzed the effect of the ethanol extract of G. verrucosa on the inhibition of the phospholipase enzyme and CSH of C. albicans. Methods: The G. verrucosa chemical compounds were examined by phytochemical tests and phospholipase enzyme-inhibiting egg yolk media, and a CSH assay was conducted using xylene. Results: Gracilaria verrucosa contains steroids, terpenoids, tannins/phenolics, and flavonoids. The 25%–100% concentrations inhibit the phospholipase enzyme of C. albicans more strongly at 48 hours than at 12 hours and 24 hours (p < 0.05). Furthermore, the 100% and 75% concentrations substantially affect the inhibition of CSH of C. albicans, with a strong relationship. Conclusion: Gracilaria verrucosa has a more substantial inhibitory effect in suppressing the phospholipase enzyme and CSH of C. albicans.